Holland Flowering : How the Dutch Flower Industry Conquered the World - Gebhardt, Andrew (Book collections on Project MUSE., 2014)
Worldwide, the indelible image of the Netherlands is the tulip. But the tulip is not alone: flowers of all kinds have long been a key part of both the Dutch identity and the Dutch economy, and in Holland Flowering, Andrew Gebhardt offers a dazzling tour of Dutch flower culture, from the earliest days of horticulture to attempts to grow bulbs on the moon. Building his account around the world's largest flower auction, Aalsmeer's, which is located near Amsterdam, Gebhardt links past and present, petals and painting, colonial trading and the European Union. The resulting book is as unusual as it is ambitious, full of insights into horticulture, the workings of markets, globalization, aesthetics, and Dutch popular culture.